'Office Exercise': Towards a more sensible boredom with technology in the office. Issue 2 (1st December 2014) - Gates, Nathan
This article is an interrogation of a small practical project I recently undertook to examine the relation between 'studio exercises', commonplace in creative practices, and 'training' that is typical of corporate environments, to see how this affects the use of technology in each context. This project titled 'Office Exercise' focuses on the relationship between the roll of 'experiment' and 'exercise' in the production of creative work involving technology. As a series of works 'Office Exercise' examines creative practice involving technology and the tensions it produces between the artistic applications of technology to a given situation and the simultaneous proficiency/competency of the use of this technology.